From the literary national wealth of the East Franconian Dialect - Corino, Karl (Acta Universitatis Lodziensis. Folia Germanica, 2018)
The article is a description of the East Franconian Dialect from the point of view of the author who grew up in the town of Ehingen. The text, written in the form of an essay, interspersed with interesting and funny descriptions of the reality of this language area, is rich in authentic examples of this dialect. For the full transparency and understanding of the dialects in the text, the author has placed a glossary at the end.